Impact of Quality Healthcare Equipment and Physical Structure on NHIS-HMO Outpatient Enrollees’ Perception in Lagos Hospitals - Abigail Affiong MKPEREDEM; Peter B. OGUNLADE; Chisaa O. IGBOLEKWU; Festus ASAMU; Bamidele RASAK; Ogadimma ARISUKWU (Communications of International Proceedings, 2020)
This study assess enrollees’ perception of Health care facility’s (HCFs) physical structure and equipment quality across 9 accredited National health insurance/ Health maintenance organisation (NHIS-HMO) providing healthcare facilities within the 3 local government areas in Lagos, Nigeria. Anchored on the phenomenology of time consciousness and the filter theory of attention, the study methodology was triangulated using survey method and in-depth interview. A total of 252 questionnaires and 5 in-depth interviews (IDIs) were used to elicit data from selected respondents using simple random and convenient sampling technique. There were differences between the survey result and the in-depth interview (IDIs) responses in terms of structural awareness in contrast with access to treatment equipments. 61.1% of the respondents agreed that the physical environment of the HCF was conducive, 61.5% agreed to the presence of standard and functional medical equipments in the HCF. With regards to the quality rating, 55.1% perceived the quality of HCFs physical structure and equipment fairly positive while 30.6% of the respondents perceived it negatively. From the group comparisons, the Chi-Square results (P
Keywords: Perception; National Health Insurance Scheme; Health Maintenance organization; Healthcare Quality.